Interior Design and Well-being: Enhancing Mental Health through Design - Rachit Sharma; Deepti Pande Rana (International Journal of Behavioral Sciences, 2024)
In contemporary society, where stressors abound and mental health concerns are prevalent, the role of interior design in promoting well-being has garnered increasing attention. This abstract provides an in-depth exploration of how strategic design interventions can positively impact mental health and enhance overall quality of life. Beginning with an examination of the psychological foundations, this abstract elucidates the intricate relationship between design elements and mental states. It discusses how factors such as lighting, color palette, spatial organization, and access to nature can influence individuals' emotional responses, cognitive functioning, and stress levels. Understanding these principles enables designers to implement targeted solutions that support mental well-being.Building upon this foundation, the abstract presents a range of actionable design strategies aimed at fostering positive mental health outcomes. One such approach is the integration of biophilic design principles, which involves incorporating elements of nature into interior spaces. Research suggests that exposure to natural elements, such as indoor plants, natural materials, and views of greenery, can reduce stress, increase productivity, and enhance mood. By embracing biophilic design, designers can create environments that evoke feelings of tranquillity, connection, and vitality. Furthermore, the abstract explores the importance of creating spaces that facilitate social interaction and community engagement. Designing communal areas with comfortable seating arrangements, inviting layouts, and amenities encourages socialization and fosters a sense of belonging. Whether in residential developments, workplaces, or healthcare settings, promoting social cohesion can mitigate feelings of loneliness and isolation, thereby promoting mental well-being.
Keywords: Mental health; color psychology; design psychology; emotional comfort; interior design; mindfulness spaces; well-being